Cultural familiarity, ethnic discrimination, and adjustment of South Asian students in South Korea - Goel, Rachit; Jaiswal, Kumkum (Journal of International Students, 2026)
This study explores the adjustment of South Asian international students in South Korea using social identity and self-determination theories. Survey data from 267 students (2024–2025) were analyzed with STATA 19.5 to examine how pre-arrival cultural familiarity, perceived ethnic discrimination, and post-arrival cultural experiences affect daily life and academic adjustment. The findings indicate that cultural familiarity positively predicts daily life and, to a lesser extent, academic adjustment. While perceived discrimination has no direct effect, post-arrival experiences, such as positive interactions with locals, social engagement, and favorable perceptions of work and education culture, significantly buffer its negative effects. Notably, perceptions of technological advancement exacerbate the adverse impact of discrimination on academic adjustment. Overall, the results emphasize the critical role of social connectedness and supportive institutional environments in fostering resilience and promoting the well-being of South Asian students adapting to South Korean higher education.